The importance and development of ball control and (self-reported) self-regulatory skills in basketball players for different positions - te Wierike, S. C. M.; Huijgen, B. C. H.; Jonker, L.; Elferink-Gemser, M. T.; Visscher, C. (Journal of Sports Sciences, 2018)
This study first investigated the importance of ball control and (self-reported) self-regulatory skills in achieving the elite level in basketball. The second aim was to gain insight into the development of, and association between ball control and (self-reported) self-regulatory skills that contribute to achieving the elite level, with taking into account positional differences. Talented male players (N = 73; age 16.56 ± 1.96) completed the STARtest to measure ball control and a questionnaire to measure (self-reported) self-regulation from 2008-2012. Results showed that (self-reported) reflective skills were most important to achieve the elite level (OR = 11.76; P < 0.05). There was no significant improvement in (self-reported) reflection over time for guards, forwards, and centers. Improvement in ball control was evident for guards (r = -0.65; P < 0.05). Furthermore, guards and forwards had better ball control compared to centers (P < 0.01). For those two positions, negative correlations were found between (self-reported) reflection and ball control, i.e., higher reflection was related to better ball control (guards r = -0.19; forwards r = -0.18) in contrast to centers (r = 0.34). It is concluded that (self-reported) reflective skills are important to achieve the elite level, while ball control seems especially important for guards.